THE IMPACT OF U.S. INTERNATIONAL MILITARY CAMPAIGN â€œWAR ON TERRORâ€ ON THE PAKISTANI CIVILIANS (A CASE STUDY : DRONES ATTACK IN PAKISTAN 2004 â€“ 2014) - Nyssa Nastasia (HI 16 UMY 047, 2016)
T*47 his undergraduate thesis on the impacts of U.S. International Military Campaign towards the Pakistani civilians with the case study of drones strikes in Pakistan from the year 2004 until 2014 aims to find out the impacts of drones strikes in Pakistan with regard to the humanity and psychological aspect of the Pakistani civilians. This research uses qualitative method from which data is collected from secondary sources such as books, news and journals. There are two framework used in this paper and that is the human security concept and a psychological theory of cognitive dissonance. The result of the research shows that not only the lives of the Pakistani civilians are lost but their humanity aspects such as economic, health, food, community are also affected in a negative way. The psychology of the Pakistani civilians are also affected in a negative way and this can lead to an increase of anti-American sentiment and may also increase terrorism.